Fit-for-purpose pharmacy workforce development in the lower middle-income country context: a mixed methods study of Nigeria - Ikhile, Ifunanya (2020)
Background The global challenge of inefficient workforce development is not equally experienced. Low and Lower-Middle Income Countries (LMICs) often have the lowest health workforce capacity yet the highest burden of disease. Pharmacists, the most accessible healthcare professionals in many LMICs, are few in number and often ill-prepared for their roles. A discrepancy between acquired and required skills are among several other challenges which continue to undermine both national health status in LMICs, as well as efforts towards the achievement of global health goals. While several studies highlight this imbalance as a major contributory factor to the poor health status in LMICs, little empiric research explores this phenomenon or identifies possible ways to address it.